PENERAPAN PEMBELAJARAN KOOPERATIF MELALUI METODE THINK PAIR AND SHARE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 3 KUALA KAPUAS - Suhadak Suhadak (Universitas Lambung Mangkurat, 2015)
This research aims to (1) increase learning motivation of students through the adoption of a model cooperative learning methods Think Pair and Share (TPS), (2) describe the use of cooperative learning methods Think Pair and Share (TPS) in class XI IIS SMAN 3 Kuala Kapuas academic year 2014/2015. This study was designed and implemented using Action Research (PTK). Research subjects are all students of Class XI IIS SMAN 3 Kuala Kapuas. Object of this research is to increase student motivation and learning activities in the application method and Think Pair Share (TPS). The instrument used in this study were (1) an instrument for measuring the activity of the teacher in the classroom who is assisted by 2 observers, (2) instrument to measure student activities, (3) instrument to measure student motivation, (4) instrument to measure student response, towards the implementation of cooperative learning model and method of Think Pair Share (TPS). PTK stages in the form of planning, implementation, observation and reflection, using a scientific approach (5M).Keywords: Cooperative Learning Model Method And Think Pair Share (TPS), student motivation, enhancing learning.